Reticulados bem arredondados e reticulados semi-estáveis no R² - Dias, Maria Paula Almeida Cavalcante [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
O objetivo deste trabalho é apresentar algumas características relacionadas à teoria de reticulados. Restringimos ao estudo dos reticulados obtidos via corpos quadráticos no R². Estudamos, de maneira sucinta, alguns conceitos básicos de álgebra e álgebra linear. Abordamos alguns resultados sobre corpos quadráticos, resultados sobre reticulados e reticulados algébricos. Focamos em duas características relacionadas a reticulados: reticulados bem arredondados e reticulados semi-estáveis.

The aim of this work is to present the study of some characteristics relatedo to theory of lattices. We restrict to the study of lattices obtained via quadratic fields in R2. We present, in a succinct way, some basic concepts of algebra and linear algebra. We approach some results on quadratic fields, results on lattices and algebraic lattices. We focus in two characteristics related to lattices: well-rounded lattices and semi-stable lattices.
Well-rounded and semi-stable lattices on R²
Keywords: Corpos quadráticos; Reticulados algébricos; Reticulados bem arredondados; Reticulados semi-estáveis; Quadratic fields; Algebraic lattices; Well rounded lattices; Semi-stable lattices